The Effectiveness of Library Instruction for Graduate/Professional Students: A Systematic Review and Meta-Analysis - Grabowsky, Adelia; Weisbrod, Liza (Evidence Based Library and Information Practice, 2020)
Objective - This study sought to assess the effectiveness of library instruction for increasing information literacy skills and/or knowledge among graduate and professional students.Methods - A search was conducted in Library Literature and Information Science Index (H. W. Wilson); Library, Information Science & Technology Abstracts; Medline; CINAHL; ERIC; Library and Information Science Abstracts (LISA); and ProQuest Dissertations and Theses Global. Studies were included if they were published between 2000 and 2019, in English, reported on library instruction for graduate or professional students, and objectively measured change in information literacy knowledge/skills.Results - Sixteen studies were included in the systematic review; 12 of the 16 studies included sufficient information to be included in the meta-analysis. The overall effect of library instruction was significant [SMD = 1.03, SE=0.19, z=5.49, P<.0001, 95% CI=0.66-1.40], meaning that on average, a student scored about one standard deviation higher on an information literacy assessment after library instruction. High heterogeneity indicated a need for subgroup analysis, which showed a significant moderation of effect by discipline of students, but none by format of instruction. However, subgroup analysis must be viewed with caution due to the small number of studies in several of the subgroups.Conclusions - This meta-analysis indicates that library instruction for graduate students is effective in increasing information literacy knowledge and/or skills. However, to strengthen the accuracy of results of future meta-analyses, there is a need for more precise descriptions of instructional sessions as well as more complete data reporting by authors of primary studies. There is also a need for the publication of more studies, particularly studies of hybrid and online instruction.